The Ehrlich Tumor Induces Pain-Like Behavior in Mice: A Novel Model of Cancer Pain for Pathophysiological Studies and Pharmacological Screening. (29th August 2013) - Calixto-Campos, Cassia; Zarpelon, Ana C.; Corrêa, Mab; Cardoso, Renato D. R.; Pinho-Ribeiro, Felipe A.; Cecchini, Rubens; Moreira, Estefania G.; Crespigio, Jefferson; Bernardy, Catia C. F.; Casagrande, Rubia; Verri, Waldiceu A.
Abstract : The Ehrlich tumor is a mammary adenocarcinoma of mice that can be developed in solid and ascitic forms depending on its administration in tissues or cavities, respectively. The present study investigates whether the subcutaneous plantar administration of the Ehrlich tumor cells induces pain-like behavior and initial pharmacological susceptibility characteristics. The Ehrlich tumor cells (1 × 10 4 –10 7 cells) induced dose-dependent mechanical hyperalgesia (electronic version of the von Frey filaments), paw edema/tumor growth (caliper), and flinches compared with the saline group between days 2 and 12. There was no difference between doses of cells regarding thermal hyperalgesia in the hot-plate test. Indomethacin (a cyclooxygenase inhibitor) and amitriptyline hydrochloride (a tricyclic antidepressant) treatments did not affect flinches or thermal and mechanical hyperalgesia. On the other hand, morphine (an opioid) inhibited the flinch behavior and the thermal and mechanical hyperalgesia. These effects of morphine on pain-like behavior were prevented by naloxone (an opioid receptor antagonist) treatment. None of the treatments affected paw edema/tumor growth. The results showed that, in addition to tumor growth, administration of the Ehrlich tumor cells may represent a novel model for the study of cancer pain, specially the pain that is susceptible to treatment with opioids, but not to cyclooxygenase inhibitor or to tricyclic antidepressant.